Pengaruh Model Problem Based Learning terhadap Keterampilan Menulis Teks Eksposisi pada Siswa Kelas VIII SMP Negeri Naiola - Opat, Ermelinda Elu; Kristanti, E; Kharisma, Giri Indra (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
Learning to write expository texts is one of the lessons that students need to master. Students are required to be able to convey strong ideas or arguments accompanied by facts in accordance with the structure and linguistic characteristics of expository texts. To achieve this goal, there needs to be an appropriate learning model. This research aims to determine the influence and response of students to the application of the Problem Based Learning model in learning to write expository texts in class VIII of SMPN Naiola, North Central Timor Regency, NTT. This research is a pre-experimental research with a one-group pretest-posttest design. Data collection is through pretest and posttest procedures as well as questionnaires. Sampling used random sampling technique. Data analysis uses descriptive statistical tests, prerequisite tests, hypothesis tests and N-Gain tests. The research results obtained a tcount value of 7,247>2,160 (ttable). Thus it can be concluded that the problem based learning model has a very significant influence in improving the ability to write expository texts with a significance value of 0.000>0.05 and students' responses to the probem based learning model are also very good.